The trajectory of inclusive beliefs in beginning teachers - Specht, Jacqueline; Delorey, Jessica; Puka, Klajdi (Frontiers in Education, 2022)
Inclusive education is supported by the belief that all students belong and are valued members of their neighbourhood school communities. Teachers must possess beliefs that support inclusion before they are able to develop the knowledge and skills necessary to implement effective inclusive practice. Using The Beliefs About Learning and Teaching Questionnaire (BLTQ), 396 participants were followed for 4 years, from their initial year in preservice teacher education through to their second year of teaching to determine the trajectory of the development of inclusive beliefs. Distinct groups were identified. Those who began with lower inclusive beliefs that tended to decrease over time were more likely to be male. Those who began with higher inclusive beliefs that remained stable were more likely to be in the elementary panel and have greater professional experience. In addition, those with higher inclusive beliefs were more likely to have greater personal experience and weeks on practicum when they began their first course in inclusive education. Results are discussed with respect to teacher education for inclusive education.